International collaboration of Polish research entities in a territorial context - Sworowska-Baranowska, Anna (Współpraca międzynarodowa polskich podmiotów badawczych w kontekście terytorialnym, 2019)
The aim of the article was to characterize the structure of scientific collaboration launched by Polish institutions in partnership with foreign entities in 2019 with a special focus on the territorial context. An analysis of the network generated on the basis of data from the POL-on system was made: weak components, the degree centrality and the betweenness centrality for each entity were identified, as well as significant connections in the network reduced to the level of countries and to voivodeships. A key entity in the network was indicated (the Central Mining Institute). Some foreign entities show high betweenness centrality in the considered network. At the level of relations between countries, the high network density and significant activity of institutions from Germany were observed, which in the future may hinder gaining advantages. Scientific collaboration of Polish institutions is carried out mainly with centres located in Europe, but it is generally not cross-border
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 130-141
Keywords: collaboration; scientometrics; SNA; współpraca; naukometria; analiza sieci